2004
DOI: 10.1038/sj.eye.6701395
|View full text |Cite
|
Sign up to set email alerts
|

Branch retinal vein occlusion treated by intravitreal triamcinolone acetonide

Abstract: Purpose To evaluate the effect of intravitreal triamcinolone acetonide on visual acuity in branch retinal vein occlusion. Methods The prospective comparative nonrandomized clinical interventional study included 28 patients (28 eyes) with branch retinal vein occlusion. The study group consisting of 10 consecutive patients received an intravitreal injection of 20-25 mg of triamcinolone acetonide. The control group including 18 patients did not receive an intravitreal injection. The mean follow-up was 8.774.4 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
1
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(102 citation statements)
references
References 55 publications
3
94
1
4
Order By: Relevance
“…[15][16][17][18] Intravitreal triamcinolone acetonide (IVTA) has been found to be effective in reducing ME and improving visual function, but its use is limited by high risk of IOP elevation and cataract progression. [15][16][17]19,20 Posterior subtenon triamcinolone acetonide (STA) has the advantage of easy injection and decreased risk of intraocular complications such as IOP elevation and cataract progression compared with IVTA, but the efficacy of STA is thought be slightly less than that of IVTA. [21][22][23] Intravitreal dexamethasone implant has recently been found to be effective in reducing ME and improving visual function.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Intravitreal triamcinolone acetonide (IVTA) has been found to be effective in reducing ME and improving visual function, but its use is limited by high risk of IOP elevation and cataract progression. [15][16][17]19,20 Posterior subtenon triamcinolone acetonide (STA) has the advantage of easy injection and decreased risk of intraocular complications such as IOP elevation and cataract progression compared with IVTA, but the efficacy of STA is thought be slightly less than that of IVTA. [21][22][23] Intravitreal dexamethasone implant has recently been found to be effective in reducing ME and improving visual function.…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal triamcinolone acetonide was first used by Antcliff to treat uveitic cystoid macular oedema; 10 consequently many scholars tried intravitreal triamcinolone acetonide to treat macular oedema associated with diabetic macular oedema, [11][12][13] proliferative diabetic retinopathy, 14 Vogt-KoyanagiHarada syndrome, 15 sympathetic ophthalmia, 16 branch retinal vein occlusion, 17 and diabetic papillopathy. 18 In addition, several case series demonstrated anatomical and vision improvement after intravitreal triamcinolone acetonide for patients with central retinal vein occlusion.…”
Section: Discussionmentioning
confidence: 99%
“…Intravitreal injection of corticosteroids, especially triamcinolone acetonide (TA), has been widely used to treat ME with diverse etiologies, including BRVO. Several authors have reported good short-and intermediate-term VA results with TA (11)(12)(13)(14)(15). Unfortunately, these studies had small numbers of patients and frequently lacked a control group for comparison.…”
Section: Salinas-alamán Et Almentioning
confidence: 99%